Formulation and characterization of surface functionalized PLGA based microparticles for in vitro stem cell survival - Uğur, Deniz (2019)
Polymeric, biodegradable and biocompatible microspheres are promising as colloidal scaffolds to deliver cells to tissues without damage and to enhance stem cell survival. It has been shown that PLGA (poly(lactic-co-glycolic acid)) based microparticles prepared by an emulsion solvent extraction technique and functionalised with ECM proteins improves stem cell adhesion and proliferation. While it is established that the presence of proteins in these systems has a biological effect, the interplay between microparticle properties and cells is poorly understood because the relationship between chemical and physical particle surface properties, protein adsorption and cell response remain unclear. Protein adsorption on a polymer particle surface is a complex phenomenon that is affected by different interfacial mechanisms/forces (e.g. DLVO and non-DLVO forces) and inherent structural properties of macromolecules (e.g. polymers, surfactants, peptides and proteins) present on surface, establishing the parameters that involves in protein/peptide adsorption on microparticles insights the logical design of the particles as a biomaterial use by contributing the understanding of another related complex phenomenon of the colloidal biomaterial-cell interface interaction in tissue engineering where limited study available to fully understand the concept. The purpose of this study is to investigate the impact of different formulation approaches on the physicochemical properties of the microparticles and identify connections between the particle properties, protein adsorption and ensuing cell response on these materials. To examine these, two different polymer types (PLGA and PLGA-P188-PLGA) and two different emulsion stabilizers; a polymeric surfactant (PVA (Polyvinyl alcohol) and a polar oil propylene glycol were used to prepare four different types of particles in an emulsion process (O/W). Particles were characterized in terms of size, charge, topography, morphology and surface chemistry to identify the effect of the variables of polymer chemistry and use of surfactant on particle properties in first part of the study. Spin coated flat polymer surfaces were generated to understand the interactions between the polymers and the proteins (fibronectin and poly-d-Lysine). For all four particle formulations; size, charge and roughness surface properties were measured. PLGA-P188-PLGA based microparticles display a higher surface roughness that was confirmed by SEM and AFM images, implying interaction with water and subsequent hydration of the particle during the emulsion which was subsequently removed during freeze-drying and caused a more pronounced topography on the particle surface. Surface roughness and microstructures is reported to enhance cell attachment in vitro by previous studies. Surfactant -free formulations (PG) have shown greater surface charge compared to the PVA based formulations before and after functionalisation, indicating steric stabilisation or residual surfactant on the surface of PVA based formulations. The presence of residual surfactant (PVA) was confirmed by ToF-SIMS and a colorimetric PVA-assay. More residual PVA was found on PLGA based particles than on P188 containing particles. Suggesting the co-solidification of polymer and surfactant during evaporation of solvent in emulsion by hydrophobic interactions and accumulation of more surfactant remaining on more hydrophobic surfaces. Identification of surfactant content of colloidal biomaterials that are formulated by emulsion technique is important to understand protein surface functionalisation and cellular response of in vitro and in vivo applications as they change the surface chemistry of the biomaterial and thus cell-biomaterial interface interactions where focal adhesion of stem cells on microparticles takes place. The adsorption of adhesion molecules to surfaces is primarily driven by the chemistry of the surface and it has been postulated that the composition of the protein solution affects the composition of proteins on the particle surfaces. To elucidate this, adsorption of fibronectin and PDL on flat PLGA and PLGA-P188-PLGA was studied by ToF-SIMS and contact angle hysteresis analysis. The contact angle hysteresis was greater for PLGA surfaces than on PLGA-P188-PLGA surfaces. Adhesion of fibronectin and PDL was found to lower the contact angle for both polymers, however varying the compositions of fibronectin and PDL in solution had not impact on the wettability of the samples. Surface functionalisation has also improved the surface charge of the PLGA microparticles by covering the inherent (i.e. acid ends) negative charge of PLGA particles into positively charged surfaces by adhesion of cationic PDL. Cationic surface charge on biomaterials is associated to cell attracting surfaces and considered as desired property of cell scaffold. Surfactant -free formulations (PG) have shown greater surface charge compared to the PVA based formulations before and after functionalisation, indicating steric stabilisation or residual surfactant on the surface of PVA based formulations. ToF-SIMS analysis of flat surfaces showed that fibronectin is primarily attracted to PLGA based hydrophobic surfaces (via hydrophobic interactions) whereas, PDL is also attracted to poloxamer containing surfaces, indicating possible electrostatic interactions between PDL and poloxamer. PVA treated flat surfaces revealed that the presence of PVA primarily limits the adhesion of fibronectin and PDL. Fibronectin -PDL (3:2, v;v) mixture was found as promising coating for particle surface based on ToF-SIMS analysis and applied to microparticle surfaces. Surface fibronectin adsorption was confirmed by anti-fibronectin immunostaining and ToF-SIMS images. Images from both techniques showed similar fibronectin distribution for identical particle formulations, suggested the stability (folded) state of the adsorbed fibronectin on particle formulations which is important to present bio-activity of surface functionalisation. When comparing the two types of polymers, fibronectin adhesion is found to be higher on PLGA based formulations while PDL is found to be higher on PG based formulations, suggesting a steric charge stabilization favoured by surfactant free (PG based) microparticle formulations. Surface functionalisation has also improved the surface charge of the microparticles by covering the inherent (i.e. acid ends) negative charge of PLGA particles into positively charged surfaces by adhesion of cationic PDL. Zeta potential measurements have showed that surfactant free formulations (PG-based) have more cationic charge compared to PVA based formulations, supporting the ToF-SIMS results of PDL adhesion. Cationic surface charge on biomaterials is associated to cell attracting surfaces and considered as desired property of cell scaffold. Human Mesenchymal Stem cell (hMSC) adhesion studies on polymer films of 2D cultures demonstrated the importance of the surface functionalisation by improving the cell adhesion on the PLGA-P188-PLGA surface. PDL coating was found to encourage the initial approach of cells to the surface; however, cells are not supported sufficiently due to the absence of ECM proteins required for the formation of stable focal adhesion with the surface. Preliminary focal adhesion study at biomaterial-cell interface based on vinculin staining is showed that surfactant present on particle surface reduces formation of focal adhesions by reducing the fibronectin adhesion compared to surfactant-free particle formulations, similarly surface hydrophilicity that arise from poloxamer moieties of triblock copolymer is also contributed in lower vinculin formation. Survival and adhesion of cells on particles are enhanced by both effective surface functionalisation with fibronectin and PDL as well as surface roughness mainly arising from the hydrophilic poloxamer segment in the PLGA triblock. These findings suggest the design of efficient microparticle formulation using an amphiphilic triblock copolymer of PLGA-P188-PLGA that is ideally rich in more hydrophobic PLGA chain and the lactic acid within PLGA, without using a polymeric surfactant (PVA) during emulsion. In this way, particles would be more effectively coated by adhesion molecules of fibronectin -PDL and the stem cell response would be enhanced by both surface functionalization and surface roughness of the microparticles. The study has outlined the parameters affecting the protein adhesion polymer particles and mesenchymal stem cell response to surface functionalized PLGA based microparticles in terms of the effect of surfactant, surface morphology, surface charge, and surface functionalization.